KONTESTASI YUDISIAL DAN INDEPENDENSI PROFESI DALAM PEMBEKUAN SUMPAH ADVOKAT: PERSPEKTIF HUKUM - Ludfi, Ludfi; Pradana, Sandi Yoga; Aini, Qurrotul; Mahbubi, Mahbubi (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2025)
This research This study examines the suspension of the oath of advocates Firdaus Oiwobo, S.H., and Razman Arif Nasution by the Ambon and Banten High Courts, in the context of the legal dialectic between the independence of the advocate profession, judicial supremacy, and contempt of court. The main issue raised is the potential conflict between the court's authority in enforcing trial discipline with the principle of due process of law and the doctrine of officium nobile which underlies the independence of advocates. This study aims to analyze the legitimacy and legal implications of the suspension of the advocate's oath and identify the potential for abuse of judicial authority. The method used is normative legal with a statutory, case, and conceptual approach, which is analyzed hermeneutically-critically. The results of the study indicate that the suspension of the advocate's oath by the high court is more than just an administrative action, but is a judicial intervention that weakens the independence of the legal profession. This action is contrary to the principles of fair trial and due process of law. This study recommends a revision of the contempt of court regulation to protect the freedom of advocates and create a balance between judicial authority and the independence of the legal profession.